Synthesis, Characterization and Biological Activity of New Ester Containing Azo Group Derived From 2-Amino-1, 3, 4-Thiadiazoline Derivatives - Ammar H. Al-Dujaili (Journal of Global Pharma Technology, 2018)
New azo compounds derived from 2-amino-1,3,4-thiadiazolines were synthesized. The cyclization reaction of thiosemicarbazones [I]a,b with the acetic anhydride lead to formation of 1,3,4-thiadiazoline compounds [II]a,b. Compounds[II]a,b were converted to 2-amino-1,3,4- thiadiazolines [III]a,b by hydrolysis of amide group using hydrazine hydrate. The new azo compounds [IV]a,b were synthesized via converted the amino group of [III]a,b to diazonium salt, follow by the reaction with 4-hydroxyphenol. Finally the ester compounds [V]a-f was synthesized from the reaction of azo compounds with suitable carboxylic acid chloride. The synthesized compounds were characterized by elemental analysis, FTIR, 1HNMR and mass spectroscopy. All these compounds were evaluated for antibacterial activity against Staphylococcus aureus, Bacillius Subtilis, Escherichia coli and Pseudomonas aeruginosa by disk diffusion method and for antifungal activity against Aspergillus niger in Sabouraudʼs dextrose agar medium. Amoxicillin and fluconazole were used as standard drugs for Gram positive, Gram negative and antifungal activity, respectively. Most of the compounds have shown significant antibacterial and antifungal activity when compared with the standard antimicrobial agents.Keywords: 1, 3, 4-Thiadiazoline; Ester compounds; Azo compounds; Antibacterial activity; Antifungal activity; Disk diffusion.